Advanced hybrid nanomaterials - Taubert, Andreas; Leroux, Fabrice; Rabu, Pierre; de Zea Bermudez, Verónica (Beilstein journal of nanotechnology, 2019)
Since these origins, the field of hybrid materials has developed into a broad scientific and technological subject including important fields such as sol–gel chemistry [4–5], polymer nanocomposites [6–7], and hybrid nanomaterials [8–9]. The main issue in this approach is to monitor and control interactions between different bricks and to understand the physico-chemical mechanisms involved at the interfaces between the individual building blocks as well as between different materials. [...]the implementation of hybrid systems in devices implies miniaturization. [...]nanostructuration or nanoarchitectonics is the core of current research in hybrid materials, and the analysis of advanced hybrid materials needs specialized experimental and theoretical techniques. Polyion complex micelles formed by complexation between poly(ethylene oxide)-b-poly(acrylic acid) (PEO-b-PAA) and an oligo-chitosan-type polyamine was used as a structure-directing agent to prepare ordered mesoporous silica materials in the work “pH-mediated control over the mesostructure of ordered mesoporous materials templated by polyion complex micelles” [22].